2011
DOI: 10.1093/ejechocard/jer022
|View full text |Cite
|
Sign up to set email alerts
|

Valvuloarterial impedance does not improve risk stratification in low-ejection fraction, low-gradient aortic stenosis: results from a multicentre study

Abstract: Increased Zva is related to low LVEF and more frequent CR on DSE in LEF/LGAS. However, Zva did not allow an accurate distinction between true and pseudo-severe AS and failed to predict operative and long-term mortality after aortic valve replacement, in LEF/LGAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Similar to our study, except for the EF criteria, Levy et al investigated the prognostic significance of Zva in 184 patients who had severe AS with decreased LVEF, and concluded that Zva did not have a prognostic role after AVR,8 which supports the results of our study, although the targeted patients had different characteristics. Another study by Jander et al 13 reported that patients with ‘low gradient’ severe AS despite preserved EF, who likely have high Zva,3 4 have a prognosis similar to patients with moderate AS in comparison to ‘high gradient’ severe AS, which suggests that prognosis may be mostly impacted by ‘valvular load’ rather than ‘arterial load’.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Similar to our study, except for the EF criteria, Levy et al investigated the prognostic significance of Zva in 184 patients who had severe AS with decreased LVEF, and concluded that Zva did not have a prognostic role after AVR,8 which supports the results of our study, although the targeted patients had different characteristics. Another study by Jander et al 13 reported that patients with ‘low gradient’ severe AS despite preserved EF, who likely have high Zva,3 4 have a prognosis similar to patients with moderate AS in comparison to ‘high gradient’ severe AS, which suggests that prognosis may be mostly impacted by ‘valvular load’ rather than ‘arterial load’.…”
Section: Discussionsupporting
confidence: 91%
“…However, it is unclear whether Zva retains its prognostic impact on survival after conventional aortic valve replacement (AVR), given continued excess of afterload in some patients 8. We hypothesised that patients with severe AS with preserved ejection fraction (EF) who have increased Zva have poorer prognosis even after successful AVR because of high-global haemodynamic load chronically causing LV myocardial structural damage and thus, the recovery of LV function and regression of LV hypertrophy is slower or irreversible.…”
Section: Introductionmentioning
confidence: 99%
“…The left ventricle, ejecting blood through a stenotic valve, needs to work against the arterial load as well . Previous study have demonstrated that a higher Zva in the context of AS was consistent with poorer survival outcomes . We found that patients who switched from low‐flow to normal‐flow AS were associated with significant reduction in Zva, although the aortic valve area and transaortic pressure indices remained similar.…”
Section: Discussionmentioning
confidence: 46%
“…This may have been due to the perception that low‐flow AS was less severe or that the prognostic implications of surgery were unclear in this subgroup. Furthermore, caution must be taken that conventional parameters of AS severity in previous study (eg, valvuloarterial impedance, aortic valve resistance, stroke work loss, systemic arterial compliance) may not be reliable in low‐flow . While otherwise useful, these conventional parameters may underestimate severity in low‐flow AS as the effect of afterload appears more significant in the low‐flow state .…”
Section: Discussionmentioning
confidence: 99%